2013
DOI: 10.4049/jimmunol.1202798
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of a Dendritic Cell Subset Expressing a Chemokine Receptor, XCR1

Abstract: Dendritic cells (DCs) consist of various subsets that play crucial roles in linking innate and adaptive immunity. In the murine spleen, CD8α+ DCs exhibit a propensity to ingest dying/dead cells, produce proinflammatory cytokines, and cross-present Ags to generate CD8+ T cell responses. To track and ablate CD8α+ DCs in vivo, we generated XCR1-venus and XCR1-DTRvenus mice, in which genes for a fluorescent protein, venus, and a fusion protein consisting of diphtheria toxin receptor and venus were knocked into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(164 citation statements)
references
References 62 publications
8
155
0
1
Order By: Relevance
“…XCR1 is a chemokine receptor expressed by mature CD8 + DC and by their migratory CD103 + counterparts, found in LN. DT treatment of XCR1-DTRvenus mice, which express the DT receptor under the XCR1 promoter, results in the elimination of CD8 + DC from the spleen (46). Consistent with the results obtained using IRF8-deficient mice infected with bloodstage PbA, PbT-II proliferation was significantly reduced in the spleen of DT-treated XCR1-DTRvenus mice, amounting to ∼30% of WT controls (Fig.…”
Section: Cd8 + DC Are the Main Apc For Pbt-ii Cellssupporting
confidence: 77%
“…XCR1 is a chemokine receptor expressed by mature CD8 + DC and by their migratory CD103 + counterparts, found in LN. DT treatment of XCR1-DTRvenus mice, which express the DT receptor under the XCR1 promoter, results in the elimination of CD8 + DC from the spleen (46). Consistent with the results obtained using IRF8-deficient mice infected with bloodstage PbA, PbT-II proliferation was significantly reduced in the spleen of DT-treated XCR1-DTRvenus mice, amounting to ∼30% of WT controls (Fig.…”
Section: Cd8 + DC Are the Main Apc For Pbt-ii Cellssupporting
confidence: 77%
“…S3B). XCR1 þ DCs is the relevant of CD8a þ subset of CD11c þ splenic DCs and are responsible for cross-presentation of exogenous antigen (22). We confirmed that XCR1 is exclusively expressed among CD8a Fig.…”
Section: Prominent Function Of Xcr1supporting
confidence: 68%
“…Ly5.1 mice and screening for the presence of Va2 and Ly5.1 and absence of Ly5.2 by flow cytometry. OT-1 TCR transgenic mice, CD11c-DTR/GFP mice (21), and XCR1-DTR-venus mice (22) and other all the mice were maintained under specific pathogen-free conditions and studied in compliance with our institutional guidelines.…”
Section: Mice and Cell Linesmentioning
confidence: 99%
“…multicolor histological images suggested that these cross-presenting DC subsets were preferentially accumulated in deep areas of the T-cell zone in the SDLNs (12). Other studies directly visualized both DC subsets by histological analyses of chemokine (C motif) receptor 1 (XCR1) expression, which is selectively and highly expressed in both LN-resident DCs and migratory DCs (13)(14)(15)(16) + T-cell activation.…”
Section: Significancementioning
confidence: 99%